REVEALING THE MINANGKABAU TRADITION (TURUN MANDI, TABUIK, AND IKAN LARANGAN) BASED ON ETHNOSCIENCE AND LOCAL WISDOM - Miftahul Husna (Pendidikan IPA, FMIPA, UNP, 2022)
This research tries to expose culture and customs in Minangkabau. Culture is that complex which comprises knowledge, belief, art, morals,, conventions, and other capacities and habits by human members of society. Tradition is an ingrained behavior that represents the supporters' existence. The Turunn traditions of Bathing, Tabuik, and Prohibited Fish are the three Minangkabau cultural practices that we looked at. This study was carried out at Lubuak Minturun, Nagari Solok (Down Mandi), and Pariaman (Tabuik) (Prohibited Fish). This investigation was carried out in September 2019. The results of the study show that culture and traditions in This mingkabau has its own purpose. Based on the results of the research into the Mandir Tradition has two purposes, first to introduce to the public that has been born new descendants of a tribe or village. The second is as a greeting congratulations to the mother who just gave birth. The Tabuik tradition has a goal, namely from commemoration of the death of the grandson of the Prophet Muhammad SAW, namely Hussein bin Ali who fell on the 10th of Muharram. The Prohibited Fish Tradition has a goal of removing impurities in river, making the stones in the river not mossy and making the river water clear.